2018
DOI: 10.18203/2394-6040.ijcmph20183965
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and compliance towards mass drug administration programme against lymphatic filariasis in Vijayapura (Bijapur) district, Karnataka, India

Abstract: Background: Lymphatic filariasis or elephantiasis is the most debilitating and disfiguring scourge among all diseases. The National Health Policy (2017) has set the goal of elimination of lymphatic filariasis in endemic pockets in India by 2017. The concept of MDA is to approach every individual in the target community and administer annual single dose of anti-filarial drugs. The objectives of the study were to assess the coverage, compliance and causes for noncompliance towards MDA in Vijayapura district and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
(6 reference statements)
2
5
4
Order By: Relevance
“…9 However considering the coverage compliance gap an effective coverage rate of only 83.2% was observed in the present study which is lesser than observed by Gudegowda KS et al, in 2016.7 Similar study conducted in Bijapur district by Kulkarni P et al, in 2017 shows a coverage rate of 80.3% and effective coverage rate of 72.5% and Waseem A et al, in 2014 shows a coverage and compliance rate of 81.63% and 79.21% respectively. 10,11 Similar to a previous study conducted by Kulkarni et al in Bijapur district in 2017, the coverage and compliance were significantly higher in rural areas compared to urban areas. Hence it proves the good impact of village level health workers like Anganwadi workers and ASHAs in mobilizing community towards MDA, which is specifically lacking in urban areas.…”
Section: Discussionsupporting
confidence: 75%
“…9 However considering the coverage compliance gap an effective coverage rate of only 83.2% was observed in the present study which is lesser than observed by Gudegowda KS et al, in 2016.7 Similar study conducted in Bijapur district by Kulkarni P et al, in 2017 shows a coverage rate of 80.3% and effective coverage rate of 72.5% and Waseem A et al, in 2014 shows a coverage and compliance rate of 81.63% and 79.21% respectively. 10,11 Similar to a previous study conducted by Kulkarni et al in Bijapur district in 2017, the coverage and compliance were significantly higher in rural areas compared to urban areas. Hence it proves the good impact of village level health workers like Anganwadi workers and ASHAs in mobilizing community towards MDA, which is specifically lacking in urban areas.…”
Section: Discussionsupporting
confidence: 75%
“…Kulkarni et al found coverage to be 80.3% and compliance to be 72.5% in Vijayapura (Bijapur) District of Karnataka which was higher than the present study. 16 Ganapa et al reported coverage rate and compliance rate79.84% and 84.6% respectively in Nalgonda district of Telangana which was also higher than the present study. 17 Kulkarni et al conducted a studyin Bagalkot District Karnataka and found coverage rate was 93.9% and effective coverage rate (compliance) was 83.2%.…”
Section: Discussioncontrasting
confidence: 74%
“…16 In contrary to other study conducted by Biradar 13 Kulkarni MM et al in their study found that only 49% of subjects had proper knowledge about the disease. 14…”
Section: Resultsmentioning
confidence: 99%